2021
DOI: 10.1089/acm.2020.0299
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Integrative Oncology Services in Australia: A Changed Mind Set Required

Abstract: Objectives: This study aimed to explore barriers and facilitators to integrative oncology (IO) service provision and access in Australia.Design: The study design was mixed method with two substudies: a cross-sectional national cancer service survey of public and private sectors; and focus group interviews and an online survey of cancer survivors. Triangulation analysis of qualitative and quantitative data was used to identify and interrogate meta-themes.Subjects: The cancer service response rate was 93.2% (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The full text of one study could not be retrieved, and 62 full-text studies failed to meet the criteria and so were eliminated. The remaining 28 studies met our criteria and had been published between 1998 and 202123–50 ((online supplemental table S1), (online supplemental file 2). Twenty-five were single-site studies, mainly from Europe (n = 8), North America (n = 7) and Oceania (n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The full text of one study could not be retrieved, and 62 full-text studies failed to meet the criteria and so were eliminated. The remaining 28 studies met our criteria and had been published between 1998 and 202123–50 ((online supplemental table S1), (online supplemental file 2). Twenty-five were single-site studies, mainly from Europe (n = 8), North America (n = 7) and Oceania (n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Eight mixed-methods studies were examined using the five relevant criteria. Three (37.5%)30 37 44 fulfilled all the criteria (online supplemental table S5), (online supplemental file 2). In all cases, if a study fulfilled all the relevant criteria, this indicated that it had high methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations